A generalized moving-boundary algorithm to predict the heat transfer rate of counterflow heat exchangers for any phase configuration. (25th March 2015) - Bell, Ian H.; Quoilin, Sylvain; Georges, Emeline; Braun, James E.; Groll, Eckhard A.; Horton, W. Travis; Lemort, Vincent
Abstract: In this work, a novel and robust solution approach is presented that can be used to predict the steady-state thermal heat transfer rate for counterflow heat exchangers with any combination of single-phase and two-phase conditions within the heat exchanger. This methodology allows for multiple internal pinching points, as well as all permutations of subcooled liquid, two-phase and superheated vapor sections for the hot and cold fluids. A residual function based on the matching of the required and available thermal conductances in each section is derived, and Brent's method is then used to drive the residual to zero. Examples are presented for the application of this methodology to a water-heated n-Propane evaporator. The computational time required to execute the model for a simple case is on the order of one millisecond when the tabular interpolation methods of CoolProp are applied. Source code for the algorithm is provided in the Python programming language as anappendix . Highlights: Generalized method presented to predict heat transfer rate of heat exchangers for all phase configurations. Considers both internal and external pinching in the heat exchanger. Bounded solver used for excellent robustness of the solution. Source code for the method is presented in the python programming language.